Institutional habitus in context: implementation, development and impacts in two compulsory secondary schools in Barcelona. Issue 8 (17th November 2017) - Tarabini, Aina; Curran, Marta; Fontdevila, Clara
Abstract: This article aims to revisit the relationship between school-level variables and students' educational opportunities through the lens of institutional habitus. This approach is particularly well suited to explore the notion of school culture because it brings to the forefront the impact of social context, avoiding some of the limitations typically associated with the long-dominant perspective of school effectiveness research. Drawing on an ethnographic approach, the article explores how institutional habitus unfolds in two urban public secondary schools in the city of Barcelona. Breaking the notion down into three main components (educational status, organizational practices and expressive order), the analysis identifies two main types of institutional habitus – one based on action and inclusion, and another based on reaction and expulsion. Ultimately, these results give insight into the complex interplay of these three components, as well as on their combined impact on students' educational opportunities.